Boundary Work and Interpretations in the IPCC Review Process of the Role of Bioenergy With Carbon Capture and Storage (BECCS) in Limiting Global Warming to 1.5°C - Hansson, Anders; Anshelm, Jonas; Fridahl, Mathias; Haikola, Simon (Frontiers in Climate, 2021)
Paris Agreement-compatible emissions pathways produced by integrated assessment models (IAMs) often rely on large amounts of CDR, especially afforestation and bioenergy with carbon capture and storage (BECCS). These pathways feature prominently in the work of the Intergovernmental Panel on Climate Change (IPCC), to the extent that the IAMs have been granted an interpretative privilege at the interface between climate science, economics, and policymaking. The privilege extends to and influences climate governance, including governance of BECCS. This paper contributes to recent debates about the role of the IPCC, and its framing of BECCS, at the science-policy interface. By analysing all BECCS-related expert review comments and author responses on the IPCC Special Report on Global Warming of 1.5°C, the paper shows that boundary work influences the representation of BECCS by authors referring to: 1) a limited scope or capacity; 2) a restrictive mandate; 3) what constitutes legitimate science, and; 4) relativizing uncertainties. The responses to the review comments indicate a significant degree of compliance on behalf of the authors. Yet, the revisions do not seem to go to the heart of the unease that runs through many of the reviewer comments, i.e. that BECCS seems to be presented as a viable CDR technology at grand scale. While several revisions serve to clarify uncertainties surrounding BECCS, some fundamental aspects of the critique are deflected, through the boundary work identified. What the analysis reveals, beyond a dissatisfaction among many reviewers with the focus on integrated assessment modelling, the associated pathway literature, and analysis of BECCS, is a disagreement about how model results should be interpreted and communicated. While acknowledging the herculean task of the IPCC and the efforts to improve the pathway literature that the SR1.5 triggered within the IAM communities, we argue that the identified boundary work also risks entrenching rather than problematize dominant framings of the feasibility of BECCS. Such entrenchment can counteract the ambition of opening up the scientific work of the IPCC to include more diversity in the process of drafting reports, and arguably also influence the governance of CDR.